PENGEMBANGAN TEMPAT PENDARATAN IKAN (TPI) DI KECAMATAN BANTAN KABUPATEN BENGKALIS PROVINSI RIAU - Zain, Jonny; Syaifuddin, Syaifuddin (Jurnal Perikanan dan Kelautan, 2014)
The study was conducted in July 2012 at the Fish Landing Places in Bantan Dis-trict on 3 units Fish Landing Places by using survey method. The aims of this study todetermine the facilities and activities as well as development possibility. The resultsshowed that the Fish Landing Places in District Bantan relatively has a few facilitiesand activities.The facilities that are available at the Fish Landing Places such as mar-keting space but the dock and fuel tanks and freshwater tanks do not all have it. Theutilization rate for each facilities generally between 3.6 to 71.66%. The Fish LandingPlaces activities are landing fish, fish marketing, supplies replenishment at sea and an-chor mooring. To develop fish landing place that needs to be done is the legality of thebusiness, adding facilities and services and to improve the quality of fish handling.